2015
DOI: 10.4236/jdm.2015.51002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Audit on the Provision of Diabetes Care in the Primary Care Setting by United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA)

Abstract: OBJECTIVE: United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) provides primary health care services including care for diabetes and hypertension, with limited resources under difficult circumstances in Gaza, West Bank, Jordan, Lebanon and Syria. A total of 114,911 people with diabetes were registered with UNRWA health centres in 2011. The aim of this cross-sectional observational study was to assess the quality of diabetes care in the UNRWA primary health care centres. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 11 publications
3
28
1
Order By: Relevance
“…All studies were published between 1992 and 2018, with thirty-three published since 2011. Thirty-eight studies reported on populations affected by armed conflict, [17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33]35,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] two reported on populations affected by natural disasters, 34,37 and one on all crisis types. 26 Thirty-four studies were conducted in the protracted crisis phase (crisis duration greater than six months), [17][18][19][20][21][22][23][24][25]…”
Section: Existing Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…All studies were published between 1992 and 2018, with thirty-three published since 2011. Thirty-eight studies reported on populations affected by armed conflict, [17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33]35,36,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] two reported on populations affected by natural disasters, 34,37 and one on all crisis types. 26 Thirty-four studies were conducted in the protracted crisis phase (crisis duration greater than six months), [17][18][19][20][21][22][23][24][25]…”
Section: Existing Evidencementioning
confidence: 99%
“…26 Thirty-four studies were conducted in the protracted crisis phase (crisis duration greater than six months), [17][18][19][20][21][22][23][24][25][27][28][29][30][31][32][33]35,[39][40][41][42][43][44][45][46][47][48]50,[52][53][54][55][56][57] three in the emergency response phase (immediate aftermath of the event up to six months), 36,49,51 two in the early recovery phase (more stable period of rebuilding up to two years following the crisis), 34,38 and two reported on multiple crises phases. 26,37 Twenty-five studies addressed refugee populations, [17][18][19][20][21]25,26,…”
Section: Existing Evidencementioning
confidence: 99%
“…However, a recent clinical audit conducted across UNRWA's operational fields identified weaknesses in lifestyle counselling and limited evidence of self-management of NCDs (32). Consistently, self-management of diabetes in Jordan and Saudi Arabia is a particular problem (33,34).…”
Section: Self-management Supportmentioning
confidence: 99%
“…Yet, progress in improving self-management and community participation raises some concerns. Patient self-management of NCDs has been weak both before and after the reform (32,46), whereas implementation of innovative and affordable communityoriented initiatives remains under consideration.…”
Section: Conclusion and Way Forwardmentioning
confidence: 99%
“…Glycemic control was assessed using participants' HbA1c measurements. Patients were considered as uncontrolled if their HbA1c is ≥7.0% and as controlled if their HbA1c is <7.0%[8] [25]. We compared mean weight, BMI, waist circumference, blood pressure, and HbA1c readings before and after the intervention using paired t-tests.…”
mentioning
confidence: 99%